2022
DOI: 10.3390/foods12010161
|View full text |Cite
|
Sign up to set email alerts
|

UHPLC-Triple-TOF-MS Characterization, Antioxidant, Antimicrobial and Antiproliferative Activity of Raspberry (Rubus idaeus L.) Seed Extracts

Abstract: The primary aim of this experiment was to investigate the bioactivity potential and polyphenolic profile of defatted raspberry seeds (DRS) extracts from three varieties (Willamette, Meeker, and Polka) using the in vitro tests HPLC-DAD and UHPLC-Triple-TOF-MS. Extracts were obtained using ultrasound-assisted extraction (UAE) or hydrolysis. The antioxidant activity of the extracts was tested using 1,1-diphenyl-2-picrylhydrazyl (DPPH), 2,2′-azinobis-(3-ethylbenzothiazoline-6-sulfonic) cation (ABTS), and ferric re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Extract with citric acid/betaine/water with molar ratio 2:1:2 exhibited the highest concentration of EA (3.20 mg/100 g extract), while extracts with tartaric acid/betaine and malic acid/betaine (both with molar ratio 2:1) showed the content of 3.18 mg/100 g extract and 3.01 mg/100 g extract, respectively. Also, Marić and coauthors prepared extracts by using an ultrasound-assisted extraction technique, and found a free EA content from 43.05 mg/100 g to 46.76 mg/100 g extracts depending of raspberry variety [19]. The content of free ellagic acid in our extracts is comparable with results from both publications.…”
Section: Determination Of Free and Total Ellagic Acid Contentsupporting
confidence: 86%
See 2 more Smart Citations
“…Extract with citric acid/betaine/water with molar ratio 2:1:2 exhibited the highest concentration of EA (3.20 mg/100 g extract), while extracts with tartaric acid/betaine and malic acid/betaine (both with molar ratio 2:1) showed the content of 3.18 mg/100 g extract and 3.01 mg/100 g extract, respectively. Also, Marić and coauthors prepared extracts by using an ultrasound-assisted extraction technique, and found a free EA content from 43.05 mg/100 g to 46.76 mg/100 g extracts depending of raspberry variety [19]. The content of free ellagic acid in our extracts is comparable with results from both publications.…”
Section: Determination Of Free and Total Ellagic Acid Contentsupporting
confidence: 86%
“…Bioactive phytochemicals from berries' seed oil processing by-products were reported for its chemical richness, heterogeneity, biological, and functional properties [18]. To date, the polyphenolic profile of defatted raspberry seeds was investigated, mainly to determine the bioactivity potential of extracts [19,20]. Marić and coauthors showed that defatted raspberry seeds extract possess high antioxidative, and high antiproliferative activities but low antimicrobial activity, and recommended that they be used in food, cosmetic, and pharmaceutical industries [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The total content of phenolic compounds determined with the Folin-Ciocalteau method confirms that raspberry fruits are a good source of antioxidant secondary metabolites [46,50,51]. The methods used, i.e., the ferric reducing antioxi-dant power (FRAP), 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical, 2,2'-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical, and OH • scavenging assays, confirm the high free radical scavenging activity of secondary metabolites from Rubi idaei fructus raw material [28,29,47,[50][51][52][53][54][55]. This indicates that raspberry fruits can be used as a valuable nutritional component in the adjuvant therapy of oxidative stress-related diseases.…”
Section: Oxidative Stress and Its Effects And Defense Mechanisms Agai...mentioning
confidence: 76%
“…Acetic acid at pH 3 promoted a better recovery of phenolic compounds of jabuticaba peels than formic acid [ 16 ], used by Quatrin et al [ 3 ] and Plaza et al [ 17 ]. Ellagic acid contents were also higher than those determined for defatted raspberry seed extracts (43.05 to 46.76 mg/100 g) obtained by ultrasound-assisted extraction [ 31 ].…”
Section: Resultsmentioning
confidence: 99%